Growth and differentiation on a trypanosome of the subgenus Schizotrypanum from the bat Phyllostomus hastatus - Sônia I. Hamanaka; Artur da S. Pinto (Revista da Sociedade Brasileira de Medicina Tropical, 1993)
The effects of temperature, pH, osmolarity and aeration on the growth and differentiation of a trypanosome ofthe subgenus Schizotrypanum isolatedfrom the bat Phyllostomus hastatus were studied. In general, the growth characteristics ofthe flagellate were similar to those of Trypanosoma (Schizotrypanum) cruzi. However, the parasite did not growth at 33 or 37C. Increase in the osmolarity and aeration promoted growth at 33C. Significant metacyclogenesis was detected only in the growth condition where maximal growth occured (28C, pH 7.3, 380m0s/kg, in tissue cullure flasks), at the end ofthe exponential growth phase. The begining of the metacyclogenesis process was coincident with most glucose utilization and lowest pH. During metacyclogenesis both culture medium pH and osmolarity increased steadly.